Exploring the Fate of Cattle Herds With Inconclusive Reactors to the Tuberculin Skin Test - Brunton, Lucy A.; Prosser, Alison; Pfeiffer, Dirk U.; Downs, Sara H. (Frontiers in Veterinary Science, 2018)
Bovine tuberculosis (TB) is an important animal health issue in many parts of the world. In England and Wales, the primary test to detect infected animals is the single intradermal comparative cervical tuberculin test, which compares immunological responses to bovine and avian tuberculins. Inconclusive test reactors (IRs) are animals that demonstrate a positive reaction to the bovine tuberculin only marginally greater than the avian reaction, so are not classified as reactors and immediately removed. In the absence of reactors in the herd, IRs are isolated, placed under movement restrictions and re-tested after 60 days. Other animals in these herds at the time of the IR result are not usually subject to movement restrictions. This could affect efforts to control TB if undetected infected cattle move out of those herds before the next TB test. To improve our understanding of the importance of IRs, this study aimed to assess whether median survival time and the rate of subsequent TB incidents differs in herds with only IRs detected compared with negative-testing herds. Survival analysis and Poisson regression were used, with herds entering the study on the date of the first whole herd test in 2012. An additional analysis was performed using an alternative entry date to try to remove the impact of IR retesting and is presented in the Supplementary Material. Survival analysis showed that the median time to failure among IR only herds was half that observed for clear herds (2.3 years and 4.3 years respectively; p<0.001). Mixed effects Poisson regression analysis showed that IR-only herds had a 54% increase in the rate of subsequent incidents compared with negative-testing herds (incidence rate ratio: 1.54; 95% CI: 1.46, 1.62; p<0.001). The supplementary analysis indicated that the fate of IR only herds is comparable to clear herds after they get through the IR testing regime. Both analyses showed that the fate of IR only herds is associated with some of the traditionally accepted risk factors for TB. This suggests that IRs may be more common among generally high-risk herds, and emphasises the importance of careful decision making around the management of IR animals.